2016
DOI: 10.1016/j.jcat.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Surface-dependent sulfidation and orientation of MoS2 slabs on alumina-supported model hydrodesulfurization catalysts

Abstract: The constant improvement of hydrotreating (HDT) catalysts, driven by industrial and environmental needs, requires a better understanding of the interactions between the oxide support (mostly alumina) and the MoS 2 active phase. Hence, this work addresses the supportdependent genesis of MoS 2 on four planar, single crystal -Al 2 O 3 surfaces with different crystal orientations (C (0001), R , M and A). In contrast to classical surface science techniques, which often rely on UHV-type deposition methods, the Mo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
55
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 60 publications
12
55
1
Order By: Relevance
“…Early reports mentioned that the catalytic performance of MoS 2 -based catalysts strongly depends on their morphology but also on the orientation, since slabs may be bonded either by the edge or by the basal planes [27] depending on the support. Usually, over gamma alumina, the preferential bonding is by the basal planes (111) and (100) since these display relatively weak and intermediate interactions with MoS 2 structures respectively as Bara et al recently showed [28]. By contrary, the plane (110) presented highly dispersed and oriented oxide particles with strong metal support interaction, the authors associated this plane with small and weakly stacked MoS 2 slabs and a very low sulfidation degree.…”
Section: The Role Of Support In the Active Sulfide Phasesmentioning
confidence: 99%
“…Early reports mentioned that the catalytic performance of MoS 2 -based catalysts strongly depends on their morphology but also on the orientation, since slabs may be bonded either by the edge or by the basal planes [27] depending on the support. Usually, over gamma alumina, the preferential bonding is by the basal planes (111) and (100) since these display relatively weak and intermediate interactions with MoS 2 structures respectively as Bara et al recently showed [28]. By contrary, the plane (110) presented highly dispersed and oriented oxide particles with strong metal support interaction, the authors associated this plane with small and weakly stacked MoS 2 slabs and a very low sulfidation degree.…”
Section: The Role Of Support In the Active Sulfide Phasesmentioning
confidence: 99%
“…At ransition from edge to basal-bondedMoS 2 was detected on the (100) plane at 773 Ksulfidation temperature, suggesting that the chemistry at the interface is not the sole determinant factor on the orientation of the MoS 2 slabs and the outcome of the molecular-scale descriptiono fa ctive phase-support interactions appearsm ultifactorial. [34] Moreover,t he precise nature of alumina thin films is still am atter of debate since Kresse et al [35] showedw ith the help of DFT that their structure and stoichiometry can be very differentf rom g-Al 2 O 3 .B ara et al [24] circumvented this issue by using a-Al 2 O 3 waferso fv arious orientationsi no rder to mimic the surfacec hemistryo fg-Al 2 O 3 . [24,25] Four different a-Al 2 O 3 orientations were used (A(112 0), C(0001), M(101 0), and R(11 02)) and their hydroxylated surface structures were comparedt o the speciation of surface hydroxyls (Al-OH)o ng-Al 2 O 3 .E xtensive experimental and modeling effort has been devoted to the description of the sorption sites on the a -Al 2 O 3 C(0001) plane, with predominantly OH groups bridging two 6-fold coordinated aluminums( Al 6c -m 2 -OH) that are also presento nt he (111)f acet of g-Al 2 O 3 .T he structure of the A(112 0), M(101 0) and R(11 02) planesh ave been less studied and therefore their surfaces tructure is still am atter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Said activation is achieved either through gas-phase or liquidphase sulphidation at temperatures of roughly 350 8C, yielding molybdenum disulphide (MoS 2 ) type particles or slabs. [5] These particles are on average smaller than 10 nm in diameter and may contain Co or Ni atoms at the particle edge positions. The latter are considered to be the primary active sites in the catalytic desulfurization reaction.…”
mentioning
confidence: 99%